Chemistry of Therapeutic Oligonucleotides That Drives Interactions with Biomolecules - Chisato Terada; Seiya Kawamoto; Asako Yamayoshi; Tsuyoshi Yamamoto (MDPI AG, 2022)
Oligonucleotide therapeutics that can modulate gene expression have been gradually developed for clinical applications over several decades. However, rapid advances have been made in recent years. Artificial nucleic acid technology has overcome many challenges, such as (1) poor target affinity and selectivity, (2) low in vivo stability, and (3) classical side effects, such as immune responses; thus, its application in a wide range of disorders has been extensively examined. However, even highly optimized oligonucleotides exhibit side effects, which limits the general use of this class of agents. In this review, we discuss the physicochemical characteristics that aid interactions between drugs and molecules that belong to living organisms. By systematically organizing the related data, we hope to explore avenues for symbiotic engineering of oligonucleotide therapeutics that will result in more effective and safer drugs.